EXHIBITION REVIEWS. Issue 2 (1st June 2013) - Cecil, Anne
McQueen's new York MoMent – a review of savage BeautY, Metropolitan MuseuM of art May 4 –July 31, 2011 and daphne Guiness, MuseuM at fit septe Mber 16 – January 7, 2012